Factors Related Factors of Malaria’s incidence in Tenateke Village, Working Area of Tenateke Health Center in Southwest Sumba Regency - Aqwinata Anggraeni Dora; Soni Doke; Johny A.R Salmun (Lontar : Journal of Community Health, 2023)
Malaria is an infectious disease caused by the genus Plasmodium transmitted to humans through the bite of a female Anopheles mosquito. Epidemiologically, conditions arise due to three crucial factors: Host, Agent, and Environmental. Environmental factors related to Malaria consist of wall density, the use of wire netting, and the presence of mosquito breeding places. This study aimed to analyze the relationship between factors of wall density, use of wire netting, and the company of mosquito breeding places with the incidence of Malaria. This type of research was an analytical survey with a case-control study design. Specific and intensive education is necessary to raise community awareness of Malaria's environmental determinants. In April, this research was conducted in Tenateke Village, Tenateke Health Center Working Area, Wewewa Selatan District, Southwest Sumba Regency. The research population was the people of Tenateke Village, who experienced cases of Malaria among as many as 65 people and 65 controls. Data was collected by using interview and observation techniques. The results of this study indicated that wall density (p-value = 0.000), use of wire netting (0.006), and the presence of mosquito breeding sites (p-value = 0.001) had a significant relationship with the incidence of Malaria.